WOMEN'S RESERVATION BILL: RHETORIC OR REALITY (NATIONAL CAPITAL LAW JOURNAL, 2008)
NA
Keywords: Women’s Reservation Bill; Gender Equality; Political Empowerment; Constitutional Amendment; Reservation for Women; Lok Sabha; State Legislative Assemblies; Panchayati Raj; Women Empowerment; Gender Discrimination; Scheduled Castes and Scheduled Tribes; Parliamentary Representation; Social Justice; Equality Before Law; Women’s Rights.